Study of People's Mining Law in Majalengka Regency - Mochamad Wildan Khaidar; Endang Sutrisno; Harmono Harmono (Eduvest - Journal of Universal Studies, 2026)
People's mining activities in Indonesia, including in Majalengka Regency, are often carried out without proper permits, leading to legal uncertainty and environmental degradation. Although regulations require environmental documents such as the Statement of Environmental Management and Monitoring Ability (SPPL) and People's Mining Permits (IPR), many small-scale miners continue to operate illegally. This research aims to analyze the position of the Statement of Environmental Management and Monitoring Ability (SPPL) and the application of sanctions against smallholder mining actors who do not have permits in Majalengka Regency. The research method used is normative juridical, examining laws and regulations, literature, and supporting data related to people's mining. The results of the study show that SPPL holds an important position as a form of environmental approval for small-scale people's mining activities that are not required to have AMDAL or UKL-UPL. However, in practice, there are still people's mining activities that operate without having a People's Mining Permit (IPR) and SPPL. This condition causes administrative violations and has the potential to result in criminal sanctions if activities continue to be carried out without permission. The Majalengka Regency Government, through Satpol PP and related agencies, has implemented administrative sanctions in the form of reprimands and closures of mine sites. This research emphasizes the importance of supervision, coaching, and coordination between agencies in order to create orderly, legal, and environmentally sound governance of people's mining.